Aplikasi Monitoring Wifi.Id PT Telekomunikasi Indonesia Berbasis Android - Riona Alpeni; Irawan Hadi; Sopian Soim (STIKOM Tunas Bangsa Pematangsiantar, 2019)
The development of telecommunications network technology in Indonesia begins with wireline to become wireless telecommunications as it is today. One of the wireless telecommunications technologies used today is Wireles Fidelity (Wi-Fi) which has the advantage of being in terms of sending signals and having a high frequency. One of the Wireless Fidelity (WiFi) service providers, namely PT Telekomunikasi Indonesia with its products, named Wifi.Id. The amount of bandwidth in the Access Point (AP) always changes according to the number of users connected to the Access Point (AP). So that PT Telekomunikasi Indonesia needs to monitor the Access Point (AP) to meet user satisfaction. In addition to Bandwidth, other parameters are also checked on the Access Point (AP), namely Service Set Identifier (SSID), Media Access Control Address (MAC Address), Received Signal Strength Indication (RSSI), Data Rate, and Frequency Access Point (AP ) which is measured in real time in the field. In this study the application was built using Android Studio which uses the Java programming language and XML, as well as for storing data using the MySQL database. The method used for building applications uses the Prototype method. The results of the research carried out are an android-based application for monitoring Access Points (AP) that can facilitate the operators of PT Telekomunikasi Indonesia.